Shifting the Balance: Heat Stress Challenges the Symbiotic Interactions of the Asian Citrus Psyllid, Diaphorina citri (Hemiptera, Liviidae) - Alda Dossi, Fabio Cleisto; Silva, Edney Pereira da [UNESP]; Consoli, Fernando Luis (Univ Chicago Press, 2018)
Global warming may impact biodiversity by disrupting biological interactions, including long-term insectmicrobe mutualistic associations. Symbiont-mediated insect tolerance to high temperatures is an ecologically important trait that significantly influences an insect's life history. Disruption of microbial symbionts that are required by insects would substantially impact their pest status. Diaphorina citri, a worldwide citrus pest, is associated with the mutualistic symbionts Candidatus Carsonella ruddii and Candidatus Profftella armatura. Wolbachia is also associated with D. citri, but its contribution to the host is unknown. Symbiont density is dependent on a range of factors, including the thermosensitivity of the host and/or symbiont to heat stress. Here, we predicted that short-term heat stress of D. citri would disrupt the hostsymbiont phenological synchrony and differentially affect the growth and density of symbionts. We investigated the effects of exposing D. citri eggs to different temperatures for different periods of time on the growth dynamics of symbionts during the nymphal development of D. citri (first instar to fifth instar) by real-time polymerase chain reaction. Symbiont densities were assessed as the number of gene copies, using specific molecular markers: 16S rRNA for Carsonella and Profftella and ftsZ for Wolbachia. Statistical modeling of the copy numbers of symbionts revealed differences in their growth patterns, particularly in the early instars of heat-shocked insects. Wolbachia was the only symbiont to benefit from heat-shock treatment. Although the symbionts responded differently to heat stress, the lack of differences in symbiont densities between treated and control late nymphs suggests the existence of an adaptive genetic process to restore phenological synchrony during the development of immatures in preparation for adult life. Our findings contribute to the understanding of the potential deleterious effects of high temperatures on host-symbiont interactions. Our data also suggest that the effects of host exposure to high temperatures in symbiont growth are highly variable and dependent on the interactions among members of the community of symbionts harbored by a host. Such dependence points to unpredictable consequences for agroecosystems worldwide due to climate change-related effects on the ecological traits of symbiont-dependent insect pests.